2001
DOI: 10.1080/09585180010027941
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of mental disorder in female remand prisons

Abstract: High rates of undetected mental disorder have been reported in male remand prisons. Little is known about the levels of mental disorder that are undetected among female remand prisoners. The aims of the study were to assess the prevalence of mental disorder in newly remanded female prisoners and the ef cacy of the prison health screen at identifying mental disorder. To achieve these aims consecutive female remand prisoners were screened for mental disorder at reception to prison. Diagnosis of mental disorder w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 9 publications
2
30
0
Order By: Relevance
“…Estimates suggest that as many as 37% of sentenced prisoners in UK prisons are suffering some form of mental illness [Birmingham et al, 2000;Gunn et al, 1991] and a recent study of female remand offenders found nearly 60% with a mental illness and 11% suffering psychosis [Parsons et al, 2001]. Whilst no remand prisoners were included in this study, these figures do suggest the potential presence of particularly high levels of mental health problems in female offenders.…”
Section: Introductionmentioning
confidence: 66%
“…Estimates suggest that as many as 37% of sentenced prisoners in UK prisons are suffering some form of mental illness [Birmingham et al, 2000;Gunn et al, 1991] and a recent study of female remand offenders found nearly 60% with a mental illness and 11% suffering psychosis [Parsons et al, 2001]. Whilst no remand prisoners were included in this study, these figures do suggest the potential presence of particularly high levels of mental health problems in female offenders.…”
Section: Introductionmentioning
confidence: 66%
“…There were a number of other reasons for exclusion: (1) failure to include the whole prison population or a random sample of this population [34–36]; (2) reporting of retrospective substance use while in prison in post‐release prisoners [37,38]; (3) reporting estimates from only prisoners selected for assessment or treatment of substance dependence [39,40]; (4) reporting of combined results for men and women [10]; (5) reporting of combined estimates for alcohol and drug misuse [41,42]; (6) greater than 50% non‐participation [43]; (7) measuring solely injectable substance use [36,39,44]; and (8) lack of standardized criteria or unclear definitions regarding either substance abuse or dependence [35,45–65]. A group of studies examining the prevalence of drug dependence as part of the Arrestee Drug Abuse Monitoring programme in the United States was excluded for this latter reason [13,14]; (9) one 1985 study that used diagnostic criteria according to the International Classification of Diseases, version 8 [66].…”
Section: Methodsmentioning
confidence: 99%
“…Fazel and Grann 23 found that 20% of homicide offenders in Sweden had a psychotic illness with 8.9% schizophrenia, 6.5% other psychosis, 1.4% drug-induced psychosis and 1% organic psychosis. Parson et al 24 found prevalence of 9.9% for schizophrenia and other psychotic disorders. This is a much higher percentage than that reported in the Fazel and Danesh review 2 as well as in our study.…”
Section: Psychosis (Schizophrenia Schizotypal and Delusional Disorder)-mentioning
confidence: 99%